(untitled) (Research, Society and Development, 2022)
The possibility of applying the theory of the loss of a chance of cure or survival has been a recurring theme in cases in which medical civil liability is discussed. Especially with regard to the evidentiary phase, the problematization is permeated in the presumptive judicial decisions, averse to the fulfillment of the substantial contradictory and procedural cooperation, culminating in the use of evidence with a non-coherent and adequate argumentative construction of medical guilt and the causal link between medical conduct and the harmful event. As a hypothesis of the stir, it is understood that the application of the requirements established by the Superior Court of Justice are an indispensable part of the theme decidendum. This study aims, in this line, to demonstrate the outstanding evidentiary procedural elements in the context of the verification of the theory of loss of a chance in the medical field, as well as to analyze to what extent the judge could use presumptive reasoning to conclude for the application of the theory in the medical field. Through a deductive analysis using national and international specialized doctrine on the subject, in addition to citing specific legislation, jurisprudence and principles of law, its application in the particular case is identified. Also, the logical and systematic methods will be used, with the demonstration of cases already decided by the national courts.